Climate change, human mobility, and conflict and fragility: An examination of dominant policy narratives in Honduras - Schapendonk, Frans; Scartozzi, Cesare M; Higuera Florez, Julian; Laderach, Peter; Pacillo, Grazia (2024)
This policy brief assesses the current state of play of the Honduran policy landscape with regards to the intersection of climate change, human mobility, and conflict and fragility. Through the deployment of an ex-ante content analysis, relevant national and sectoral policy and strategy documents are assessed to identify, firstly, whether the climate-mobility- fragility nexus features as a strategic consideration across various sectoral policy agendas within Honduras, and secondly, detect dominant narrative framings of the nexus within the policy discourse. We find that a central tenet of Honduran policy discourse around the intersection of climate change, human mobility, and conflict and fragility is an overarching concern with rapid and unplanned migration into urban settings, irregular migratory movements, and the impact of extreme weather events. In line with broader regional trends, Honduran policy discourse moreover tends to deploy existing legal and ontological categorisations such as refugee and asylum seeker even when climate-related mobility drivers are apparent. Finally, evidence of a coherent cross-sectoral discursive framing and policy approach to the nexus is largely absent.